The Financial Performance Comparison of Islamic Bank in Indonesia with Islamic Bank in UK - Dovi Septiari; Raja Nur Mazlifani (Pusat P2M Politeknik Negeri Batam, 2018)
The purpose of this study was to determine how the performance difference between Islamic banks in Indonesia by Islamic banks in the UK, which has cultural and religious backgrounds are different from each other. In this study use financial statements of Islamic banking in Indonesia and in the United Kingdom in the five-year period, existing data will be processed and calculated its financial performance using the Mann-Whitney U test using SPSS data processing tools. The results of this study found that there are differences in terms of profit and there is no difference in terms of capital structure in Islamic banks in Indonesia by Islamic banks in the UK. In this study, there are some limitations as to the number of samples is very little, many companies do not publish their financial statements, many companies that do not have separate financial statements (non-consolidated). The implications of this study showed that the difference of financial performance in Islamic banks in Indonesia by Islamic banks in the UK, this difference could have occurred because of cultural and religious backgrounds are different from each other between Indonesia and the UK. Suggestions for further research are expected to increase the number of samples in which more like adding a non-Muslim state in Europe, and also increase the ratio of the value of performance measurement used in comparing the financial performance of banks.